CAD/Tolerancing integration: Mechanical assembly with form defects. (December 2017) - Jbira, I.; Tlija, M.; Louhichi, B.; Tahan, A.
Highlights: Tolerance Integration in CAD model; Modeling of components with form defects; Modeling of realistic planar and cylindrical joints; The realistic modeling of the parts and assemblies; Joint behavior of realistic components during assembly operation. Abstract: Geometric deviations affect the assemblability and functional compliance of products, since small part variations accumulate through large-scale assemblies and lead to malfunctions. The Digital Muck Up (DMU) upgrade requires a tolerance consideration in CAD models. The improvement of tolerancing leads to industrial success. Therefore, improving the CAD model to be closer to the realistic model is a necessity to verify and validate the mechanical system assemblability. In previous work, an approach to consider the dimensional, positional and orientation tolerances in CAD models was developed. In this paper, the above approach is improved to take into account form defects in CAD models. To model the component with form defects, the toleranced face is modeled by gird vertices. According to form tolerance values, a White Gaussian Noise (WGN) of gird vertices is computed. The realistic face is obtained by an interpolation based on the tessellation using Thin Plate Surface (TPS) modeling. The realistic assembly configurations were performed by updating the mating constraints. In fact, in realistic modeling, a new method to redefine constraints, while respecting the Objective Function of the Assembly (OFA), is established. In the case of a planar joint, a sub-algorithm based on Oriented Bounding Box (OBB) and the matrix transformation is developed. Relative part displacements are simulated with or without guaranteeing contact. Tolerance impacts on the realistic assembly motion are quantified. The realistic cylindrical joint is performed using an optimization method: the minimum cylinder inside a realistic hole and the maximum cylinder outside a realistic pin. Finally, in the case of a revolute joint, a sub-algorithm to redefine the mating constraints between two realistic parts is performed. This paper proposes a new approach to incorporate tolerances on CAD models in the case of planar and cylindrical faces by determining configurations with positional, orientation and form defects. This approach provides an assembly result closer to the real assembly of the mechanical system. Integrating tolerances in CAD allows the simulation and visualization of the mechanical assemblies' behavior in their real configurations.